2014
DOI: 10.3109/01443615.2014.960826
|View full text |Cite
|
Sign up to set email alerts
|

Female genital cutting: A survey among healthcare professionals in Italy

Abstract: This study aims to evaluate the knowledge of female genital cutting (FGC) in a tertiary teaching hospital in Italy. A survey questionnaire on FGC was given to paediatricians, nurses, midwives, gynaecologists and residents in paediatrics and gynaecology in a tertiary teaching hospital in Italy. The results of the survey were then analysed. The results showed that 71.5% (73/102) of healthcare professionals dealt with patients presenting with FGC. Gynaecologists (83%) and paediatric nurses (75%) were the only one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 14 publications
2
11
0
Order By: Relevance
“…We also demonstrated that positive family history of FGM/C in grandmother, mother, and sister is significantly associated with higher prevalence of FGM/C. Consistent with previous reports, we found that type I FGM/C was the most common performed procedure in the region [1,13,14,17,20,24]. However, clitoral nicking was even more common.…”
Section: Discussionsupporting
confidence: 91%
“…We also demonstrated that positive family history of FGM/C in grandmother, mother, and sister is significantly associated with higher prevalence of FGM/C. Consistent with previous reports, we found that type I FGM/C was the most common performed procedure in the region [1,13,14,17,20,24]. However, clitoral nicking was even more common.…”
Section: Discussionsupporting
confidence: 91%
“…The findings of this survey underline the increased need for further training on FGM as it has been suggested by other studies in Australia (17,33). Likewise, other HIC such as the UK (24,27), US (18), Sweden (20) and Italy (34,35) also emphasised the need for specialised skills for healthcare professionals who care for women with FGM during pregnancy and childbirth. Australian midwives expressed the need for more comprehensive and specialised training as part of pre-service and inservice midwifery training (33).…”
Section: Discussionsupporting
confidence: 55%
“…However, approximately 80% of the study participants had encountered and cared for women with FGM during their practice (24). Similarly, studies in Italy (34,35), Sweden (20), the United States of America (USA) (18) and Spain (36) have also reported poor of health provider knowledge of FGM.…”
Section: Discussionmentioning
confidence: 98%
“…These negative experiences and othering may result not only from a lack of training specific to FGC [ 48 , 49 , 50 , 51 ] but also from health care practitioners not knowing what to do when faced with a patient with FGC [ 52 , 53 ]. This suggests a need for training vis-à-vis treatment of reproductive healthcare for women with FGC and a health care system that does not make women with FGC feel abnormal.…”
Section: Resultsmentioning
confidence: 99%